2016
DOI: 10.1016/j.reth.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibroblast-derived VCAM-1 enhances cardiomyocyte proliferation for fabrication of bioengineered cardiac tissue

Abstract: Background Fibroblasts are indispensable for the fabrication of cell-sheet–based bioengineered cardiac tissues; however, whether cardiac fibroblasts can improve tissue properties for transplantation or in vitro models compared with other fibroblast types remains unclear. We compared the cell organization and functional properties of cardiomyocyte sheets derived from co-culture with different fibroblast types and investigated the molecular mechanisms for the observed diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 27 publications
(36 reference statements)
0
25
0
Order By: Relevance
“…VCAM1 is the ligand for α4β1 integrin, which is known to exist as both a transmembrane protein and in a soluble form. Several groups, including ours, have reported that VCAM1 is expressed in cardiomyocytes [66], CSCs [2], and CFs [67]. Soluble VCAM1 secreted from murine CSCs demonstrated cardioprotective effects in mouse through the α4β1 integrin-mediated activation of Akt, ERK, and P38MAPK in cardiomyocytes [2]; this phenomenon has also been reported to be critical for heart development [68,69].…”
Section: Discussionmentioning
confidence: 87%
“…VCAM1 is the ligand for α4β1 integrin, which is known to exist as both a transmembrane protein and in a soluble form. Several groups, including ours, have reported that VCAM1 is expressed in cardiomyocytes [66], CSCs [2], and CFs [67]. Soluble VCAM1 secreted from murine CSCs demonstrated cardioprotective effects in mouse through the α4β1 integrin-mediated activation of Akt, ERK, and P38MAPK in cardiomyocytes [2]; this phenomenon has also been reported to be critical for heart development [68,69].…”
Section: Discussionmentioning
confidence: 87%
“…It is unclear if the dermal fibroblast origin of our derived hiPSC‐CM could have played a role in such reduced remodelling capacity of fibroblasts co‐derived during cardiac differentiation. Nevertheless, dermal fibroblasts were recently reported to be less supportive of bioengineered cardiac tissue formation when compared to cardiac fibroblasts (Iwamiya, Matsuura, Masuda, Shimizu, & Okano, ).…”
Section: Resultsmentioning
confidence: 99%
“…Our data on the composition of platelet releasate revealed that known key growth factors driving myoblast and/or chondrocyte proliferation such as PDGFBB and VEGFA were increased several fold in SR (Kieswetter, Schwartz, Alderete, Dean, & Boyan, ; Scully, Sfyri, et al, ). VCAM‐1 was previously shown to increase cardiomyocyte proliferation and skeletal myoblast differentiation and was 3.8‐fold more abundant in SR compared with physiological releasate (Choo, Canner, Vest, Thompson, & Pavlath, ; Iwamiya, Matsuura, Masuda, Shimizu, & Okano, ). Similarly, growth factors driving fibroblast proliferation such as EGF and FGF‐2 were increased 1.92‐ and 3.43‐fold, respectively (Yu, Matsuda, Takeda, Uchinuma, & Kuroyanagi, ).…”
Section: Discussionmentioning
confidence: 99%